1996
DOI: 10.1111/j.1558-5646.1996.tb02361.x
|View full text |Cite
|
Sign up to set email alerts
|

WITHIN‐ AND BETWEEN‐GENERATION EFFECTS OF TEMPERATURE ON THE MORPHOLOGY AND PHYSIOLOGY OF DROSOPHILA MELANOGASTER

Abstract: Abstract,-We investigated the effects of developmental and parental temperatures on several physiological and morphological traits of adult Drosophila melanogaster. Flies for the parental generation were raised at either low or moderate temperature (18°C or 25°C) and then mated in the four possible sex-by-parental temperature crosses. Their offspring were raised at either 18°C or 25°C and then scored as adults for morphological (dry body mass, wing size, and abdominal melanization [females only]), physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
124
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 94 publications
12
124
0
Order By: Relevance
“…Studies on natural populations of chorus frogs (Pseudacris triseriata) and wood frogs have also demonstrated that frogs metamorphosing later and of smaller mass experience lower survival in the wild, although the cause of this lower survival rate is not clear (Smith 1983;Berven 1990). Studies on other taxa have shown that phenotypic plasticity exhibited early in ontogeny can affect traits (Taylor 1988;Milbrath et al 1993;Crill et al 1996;de Moed et al 1997) and performance (Ravelli et al 1976;Woollacott et al 1989;Haywood and Perrins 1992;Merilä and Svensson 1997;Pechenik et al 1996b) later in ontogeny, but rarely do we observe such dramatic and rapid impacts of larval environments on juvenile survival.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies on natural populations of chorus frogs (Pseudacris triseriata) and wood frogs have also demonstrated that frogs metamorphosing later and of smaller mass experience lower survival in the wild, although the cause of this lower survival rate is not clear (Smith 1983;Berven 1990). Studies on other taxa have shown that phenotypic plasticity exhibited early in ontogeny can affect traits (Taylor 1988;Milbrath et al 1993;Crill et al 1996;de Moed et al 1997) and performance (Ravelli et al 1976;Woollacott et al 1989;Haywood and Perrins 1992;Merilä and Svensson 1997;Pechenik et al 1996b) later in ontogeny, but rarely do we observe such dramatic and rapid impacts of larval environments on juvenile survival.…”
Section: Discussionmentioning
confidence: 94%
“…While we have abundant evidence that early environments can affect subsequent performance (growth, fecundity, and survival), we have a poor understanding of the underlying mechanisms that are responsible. One reason for this poor understanding is that few investigators examine the behavioral, physiological, and morphological traits expressed both early and later on in ontogeny (but see Tollrian 1995;Crill et al 1996;de Moed et al 1997), even though these trait changes are what collectively determine performance. Thus, we need to know how early environments affect both the subsequent traits of individuals as well as the subsequent performance of individuals.…”
Section: Introductionmentioning
confidence: 98%
“…In ectotherms, some traits important in locomotion, such as the number of body segments and muscle structure, are highly responsive to the temperature experienced early in development (e.g. Lindsey 1966;Lindsey and Harrington 1972;Stickland et al 1988;Shine and Harlow 1993;Partridge et al 1994;Crill et al 1996;Johnston and McLay 1997). Temperatures close to the upper and lower thermal tolerance limits generate a high probability for phenodeviants as a result of developmental stress (Smith-Gill 1983;Møller and Swaddle 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, geographic variation in metabolic rates can be related to a high thermal sensitivity during early stages of development. The temperature of embryonic development can induce long-lasting or permanent phenotypic change in morphology and muscle structure (Ta˚ning, 1952;Crill et al, 1996). This source of developmental instability can have an influence on metabolic rates.…”
Section: Introductionmentioning
confidence: 99%